An offer you can't refuse: Murdering journalists as an enforcement mechanism of corrupt deals - Christian Bjørnskov; Andreas Freytag (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
Anecdotal evidence suggests that journalists and bureaucrats in some countries are killed when they try to blow the whistle on corruption. We demonstrate in a simple game-theoretical model how murders can serve as an enforcement mechanism of corrupt deals under certain regime assumptions. Testing the main implications in an unbalanced panel of 179 countries observed through three periods, we find that corruption is strongly related to the incidence of murders on journalists in countries with almost full press freedom. While our results provide evidence that journalists are killed for corrupt reasons, they also suggest that some countries may have to go through violent periods when seeking to secure full freedom for the press.
Keywords: D73; 330; corruption; rent-seeking; murder; Korruption; Rent Seeking; Spieltheorie; Gewalt